Evolutionary interactions of brood parasites and their hosts : recognition, communication and breeding biology : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Ecology at Massey University, Auckland, New Zealand - Anderson, Michael Gareth (Massey University, 2009)
Obligate brood parasites lay their eggs in nests of other species, relying on these host parents to care for their offspring. This phenomenon has been a curiosity amongst researchers since its first description and has become a model study system for testing such ideas as coevolution and species recognition. This thesis examines a few of the many questions that arise from this breeding system. The New Zealand Grey Warbler (Gerygone igata) and its brood parasite, the Shining Cuckoo (Chrysococcyx lucidus) are used as the main study species, although research on the eviction behaviour of Common Cuckoos (Cuculus canorus) has also been conducted. First, the current state of knowledge and recent discoveries regarding nestling rejection abilities of hosts is reviewed in chapter one. Second, a comparative study of New Zealand passerine begging calls has been conducted to test for begging call similarity between a brood parasite and its host, as well as developing a new technique for detecting the mode of coevolution that may be occurring in the parasite – host relationship. Parent-offspring communication in Grey Warblers is also examined to test for both parental and nestlings Parents use both alarm calls to warn offspring of potential danger, and also parental feeding calls to elicit a begging response from nestlings. By contrast, nestlings are able to signal both age and short term levels of need to parents through the acoustic structure of the begging call. The evolutionary costs and benefits of egg eviction behaviour in the Common Cuckoo are also tested. An experimental approach showed that egg eviction had a growth cost, but this cost was temporary and restricted to during and immediately after the egg eviction phase. A pattern of compensatory growth was observed after the eviction period, so that during the later nestling stages there was no difference in mass, and no difference in fledging age. Finally, variation in the Grey Warbler breeding biology and Shining Cuckoo parasitism rates are examined through both time and across latitudes. This research has shown a counterintuitive pattern of breeding phenology across latitudes. These patterns have implications for Shining Cuckoos both in terms of timing of available nests and host selection. Keywords: Begging call, breeding phenology, brood parasitism, coevolution, Common Cuckoo, eviction, Grey Warbler, parent-offspring communication, Shining Cuckoo.
Keywords: Brood parasitism; Co-evolution; Grey warbler; Shining cuckoo; Fields of Research::270000 Biological Sciences::270700 Ecology and Evolution::270703 Terrestrial ecology